Effect of Bi/Ti ratio on (Na0.5Bi0.5)TiO3/Bi4Ti3O12 heterojunction formation and photocatalytic performance. Issue 6 (December 2021) - Jiang, Yue; Chen, Wen-Fan; Ma, Hongyang; Ren, Hangjuan; Lim, Sean; Lu, Xinxin; Bahmanrokh, Ghazaleh; Mofarah, Sajjad S.; Wang, Danyang; Koshy, Pramod; Sorrell, Charles C.
Abstract: Bismuth-based metal oxide compounds are promising candidates as novel photocatalysts for environmental remediation. However, their low quantum efficiencies and rapid electron-hole recombination times have hindered their uptake for photocatalytic applications. The present work reports an investigation of the effects of variable Bi/Ti ratio during hydrothermal synthesis on the phase assemblage, nanostructure, surface chemistry, band gap, and photocatalytic performance. Increasing Ti concentration resulted in variations in characteristics and properties according to the sequential formation of the principal phases α-Bi2 O3 (BO), Bi4 Ti3 O12 (BTO), and (Na0.5 Bi0.5 )TiO3 (NBT). Samples fabricated with precursors having a Bi/Ti ratio of 12/12 exhibited the highest methylene blue (MB) photodegradation rate of 92% under UV irradiation for 2 h. This excellent photocatalytic performance is attributed to the formation of an NBT/BTO heterojunction with advantageous band alignment. Graphical Abstract: ga1 Highlights: The phase assemblage shifted from Bi2 O3 to BTO to NBT with increasing Bi/Ti ratio. The photocatalytic performance was dominated by the heterojunctions of BTO on NBT. The importance of the heterojunctions was verified by the improved charge transfer.